Figuração da paisagem: percepção da geograficidade em Vidas secas e Os flagelados do vento leste - Freitas, Luís Oliveira (2017)
This presente study aims to analyze the geographycity in two important Literature books in portuguese language named Vidas secas, by the brazilian author Graciliano Ramos and Os flagelados do vento leste, by the Capeverdian writer Manuel Lopes. The brazilian novel portraits a countryside family which has a hard life in the northeastern backwoods due to the drought phenomenon that reaches the region where these people live and, because of that, they move to other regions in search of surviving.The Capeverdian book points out a sad scenery in which the drought reaches all aspects of life of the characters forcing them to be reduced to the removers plagued condition by hunger. The analysis will be done based on the principles and concepts of the Cultural Humanist Geography, in which discussions related to landscape, space, place, topophilia, topophobia,perception and experience will be held in the light of this Humanist bias of phenomenological-existential basis, developted, by Eric Dardel, YiFu Tuan, Edward Relph and others. The Geography and Literature specificities will be showed as well as the contacts and distance aspects between these two study areas. It will be emphasized the historical, social and cultural contextualization of both books, based on their aesthetic-literary value.